(untitled) (Research, Society and Development, 2021)
Currently, the diversity of forms of therapeutic treatment for autistic children provides various possibilities of resources. In this sense, horse therapy is highlighted as a tool within a complementary and interdisciplinary approach. Studies on horse therapy point out the contribution to autonomy and motor skills, to be considered effective the physical space needs to have architectural elements with the purpose of ensuring inclusion. The objective of this article is to discuss the challenges of inclusive architecture in equotherapy centers. To this end, the methodology used is based on an exploratory bibliographic research applied to practical and case study, with the intention of identifying problems and collecting data on physical structures of horse-riding centers in Vitoria da Conquista situated in the state of Bahia. In the end, the results pointed out the existence of legislation that guarantees inclusion, however, perceives the need to think and often adapt the physical spaces of therapeutic centers, in order to enable autistic children the right to enjoy inclusive environments. Thus, it is concluded that inclusive architecture is the possible way to ensure autistic children the best way to help them face the obstacles they experience, as well as to provide hospitality and accessibility in equine therapy centers.